Correlations between lncRNA-SOX2OT polymorphism and susceptibility to breast cancer in a Chinese population. (March 2017) - Tang, Xiuwu; Gao, Yan; Yu, Linxiang; Lu, Yan; Zhou, Guanglin; Cheng, Lifang; Sun, Kai; Zhu, Baoli; Xu, Ming; Liu, Jingjing
Aim: We evaluated the effect of lncRNA SOX2OT expression and its SNP in tumorigenesis and development of breast cancer (BC) in a case-control study.Methods: A total of 1106 individuals, 505 newly diagnosed BC patients and 601 age-matched controls (±2 years) were testified. Real-time PCR was adopted for testing tissues' SOX2OT expression. Genotyping of rs9839776 were conducted by using SNaPshot assays.Results: SOX2OT were overexpressed in BC tissues (p < 0.001). SOX2OT SNP rs9839776 was strongly associated with the higher expression of SOX2OT and an increased risk of BC in Chinese women (odds ratio: 1.42; 95% CI: 1.06–1.90; p = 0.018).Conclusion: These results confirmed that BC was conspicuously associated with higher SOX2OT expression. SOX2OT SNP rs9839776 was significantly associated with the onset of BC possibly via influencing the expression of SOX2OT.